(untitled) (International Journal of Plant Biology, 2014)
In this work, specific concentrations of cadmium, copper and zinc in double combination, were supplied for 12 days to growing seedlings of the model species Arabidopsis thaliana. Metal accumulation was measured in roots and shoots. Microscopic analyses revealed that root morphology was affected by metals, and that the root and shoot levels of indole-3-acetic acid, trans-zeatin riboside and dihydrozeatin riboside varied accordingly. Minor modifications in gibberellic acid levels occurred in the Zinc treatments, whereas abscisic acid level did not change after the exposition to metals. Reverse transcription polymerase chain reaction analysis of some genes involved in auxin and cytokinin synthesis (AtAAO, AtNIT and AtIPT) revealed that their expression were not affected by metal treatments. The root morphological alterations that resulted in an increased surface area, due to the formation of root hairs and lateral roots, could be signs of the response to metal stress in terms of a functionally-addressed reorientation of root growth. The root system plasticity observed could be important for better understanding the manner in which the root architecture is shaped by environmental and hormonal stimuli.